New palaeomacromiid dragonflies from the upper Paleocene of Argentina - Petrulevicius, Julián F. (2002)
A new genus of palaeomacromiid dragonflies, Curviarculia, based on Curviarculia delicata sp. nov. and Curviarculia lamasi sp. nov., is erected from the upper Paleocene Maíz Gordo Formation of north-western Argentina. Phylogenetic relationships within Palaeomacromiidae are discussed, leading to a new family diagnosis.